2014
DOI: 10.3109/0284186x.2014.925579
|View full text |Cite
|
Sign up to set email alerts
|

CT-planned internal mammary node radiotherapy in the DBCG-IMN study: Benefit versus potentially harmful effects

Abstract: background. The DBCG-IMN is a nationwide population-based cohort study on the effect of internal mammary node radiotherapy (IMN-RT) in patients with node positive early breast cancer. Due to the risk of RT-induced heart disease, only patients with right-sided breast cancer received IMN-RT, whereas patients with left-sided breast cancer did not. At seven-year median follow-up, a 3% gain in overall survival with IMN-RT has been reported. This study estimates IMN doses and doses to organs at risk (OAR) in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…However, the recent results from the Danish population-based study in which patients with left-sided node-positive breast cancer underwent only medial supraclavicular irradiation, whereas patients with right-sided node-positive breast cancer underwent both internal mammary and medial supraclavicular irradiation, support the role of including the internal mammary chain in the success of regional nodal radiation therapy. 39,40 When our trial was designed, adjuvant systemic therapy was not as variable as it is today and molecular subtypes were not yet described; thus, we recorded little information about these variables (Table S3 in the Supplementary Appendix). In the current study, the number needed to treat to avoid one death from breast cancer was 39, and the number needed to treat to avoid one relapse of breast cancer was 30.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent results from the Danish population-based study in which patients with left-sided node-positive breast cancer underwent only medial supraclavicular irradiation, whereas patients with right-sided node-positive breast cancer underwent both internal mammary and medial supraclavicular irradiation, support the role of including the internal mammary chain in the success of regional nodal radiation therapy. 39,40 When our trial was designed, adjuvant systemic therapy was not as variable as it is today and molecular subtypes were not yet described; thus, we recorded little information about these variables (Table S3 in the Supplementary Appendix). In the current study, the number needed to treat to avoid one death from breast cancer was 39, and the number needed to treat to avoid one relapse of breast cancer was 30.…”
Section: Discussionmentioning
confidence: 99%
“…Improved target volume coverage Given these and other potential toxicities of treatment, radiation oncologists may compromise coverage of areas at risk of harboring microscopic breast cancer in order to minimize dose to normal tissues [31]. For example, a retrospective review of previously treated plans in the modern era demonstrated mean coverage of expertly defined consensus target volumes ranging from just 74-96% [32].…”
Section: Second Malignancymentioning
confidence: 99%
“…For example, a prospective population based cohort study recently showed a 3.7% absolute survival advantage at 8 years in patients with right breast cancer who received IMN irradiation compared with left-sided breast cancer patients who did not [36]. Therefore, compromises in target coverage could increase the risk of recurrence [31]. Numerous dosimetric studies clearly support the advantage of PBT at improving target coverage while simultaneously decreasing dose to the heart, coronary vessels, lungs and contralateral normal tissue compared with photon advanced planning techniques.…”
Section: Second Malignancymentioning
confidence: 99%
“…The advances in the sentinel lymph node biopsy (SLN) procedure have led to a re-evaluation of the role of the SLN for staging IMLN basin [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In addition, few recent clinical trials demonstrate that post-mastectomy irradiation of IMLNs significantly improved the metastasis-free overall survival of patients with stage I-III breast cancer [34][35][36].…”
Section: Introductionmentioning
confidence: 99%